2022
DOI: 10.1111/eea.13248
|View full text |Cite
|
Sign up to set email alerts
|

Flight muscle structure and flight capacity of females of the long‐distance migratory armyworm,Spodoptera frugiperda: effect of aging and reproduction, and trade‐offs between flight and fecundity

Abstract: Insects in flight achieve the highest metabolism rates and wing beat frequency known in the animal kingdom, but how they do this is not fully understood. Here, we demonstrate the structure and arrangement of flight muscles in the thorax of Spodoptera frugiperda Smith & Abbot (Lepidoptera: Noctuidae). Dorsoventral direct flight muscles are stronger and more complicated than dorsoventral indirect flight muscles, which may be important for the moth to swiftly control the trajectory. The abundance of giant mitocho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…In our study, no mating behavior was observed in the S. litura exposed to the risk of predation by bats, but egg production was observed, which could be the S. litura started to lay eggs at one point, whether they were mated or not, and thus these eggs were unfertilized, which may explain why the predation risk reduces the hatching rate of the egg of the S. litura. Additionally, a trade-off might occur between reproduction and immunity in insects (Schwenke et al, 2016;Guo et al, 2022). Mating promotes reproductive activity, and an increase in reproductive activity might decrease immune function (Gao et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, no mating behavior was observed in the S. litura exposed to the risk of predation by bats, but egg production was observed, which could be the S. litura started to lay eggs at one point, whether they were mated or not, and thus these eggs were unfertilized, which may explain why the predation risk reduces the hatching rate of the egg of the S. litura. Additionally, a trade-off might occur between reproduction and immunity in insects (Schwenke et al, 2016;Guo et al, 2022). Mating promotes reproductive activity, and an increase in reproductive activity might decrease immune function (Gao et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Of which, COG and eggNOG enrichment analysis results was performed that many DEGs were enriched in the “Lipid pathway transport and metabolism” pathway; KEGG enrichment analysis also showed that relative majority DEGs were enriched in the “Fatty acid metabolism” and “Fatty acid degradation” pathways. Studies have indicated that fatty acid metabolism is an important metabolic mode for long-distance migration of insects ( Arrese and Soulages, 2010 ; Guo et al, 2022 ), combined with the pattern of flight muscle histolysis after migration ( Feng et al, 2019 ), it can be inferred that compared with other metabolic pathways, fatty acid metabolic pathway is more likely to be a regulatory pathway involved in and regulating flight muscle histolysis, and fatty acid transporters are more likely to act as regulatory signals than other proteins with fixed metabolic functions due to their properties of transporting fatty acids. In addition, it is reported that FABP has also been reported to be crucial for long-distance migration of migratory locusts ( Rajapakse et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The relationships between flight muscle and flight ability and between energy accumulation and consumption during flying ( Liu et al, 2008 ; Dou et al, 2017 ; Cao and Jin, 2020 ). The relationship between flight muscle development and reproductive system development ( Roff and Fairbairn, 2007 ; Zhao et al, 2010 ; Chang et al, 2021 ; Guo et al, 2022 ), especially the trade-off between flight capability and reproduction in female insects ( Ge et al, 2021 ). (3) The effects of insecticides on flight muscles in the context of pest control ( Liu et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The activity of all the five tested enzymes (HOAD, GPDH, GAPDH, CS and LDH) increased with age in S. frugiperda ( Figure 11 ), which is contrary to the result found in Bactrocera dorsalis [ 15 ]. S. frugiperda is a long distance migrator, younger adults have higher flight capacity, with 3-day-olds showing the highest flight capacity, while old (11-day-old) females still have strong flight capacity [ 27 ]. A higher activity of enzymes in aged adults may be important to guarantee a high flight capacity.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of long-distance migration is the key determinant of invasion status and evolutionary success of S. frugiperda [ 26 ]. Our previous study had revealed the flight capacity and flight muscle structure of S. frugiperda females [ 27 ], which provide a good basis for our in-depth research in this field. Moreover, the aging-related transcriptional changes and enzyme activity in the flight muscle of S. frugiperda females have not been investigated.…”
Section: Introductionmentioning
confidence: 99%